1976
DOI: 10.1128/iai.13.5.1522-1524.1976
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans dextransucrase: availability of disaggregated enzyme after growth in a chemically defined medium

Abstract: The soluble dextransucrase (EC 2.4.1.5) activity produced by Streptococcus mutans strain 6715 during growth on a chemically defined synthetic medium (FMS) was compared to enzyme from glucose broth cultures (TSB). Growth on the two media was similar. The specific activity of ammonium sulfate-precipitated FMC enzyme was 17 times greater than similar TSB enzyme preparations. The FMC enzyme was stimulated 11-fold, whereas the TSB enzyme was stimulated 1.2-fold by the addition of exogenous primer dextran. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…When S. mutans was grown in sucrosefree TTY broth, significantly higher GTase activity was detected in the culture supernatant as compared with several commercial broth media, except BHI (Table 2). Other investigators (3,11,16,23) also demonstrated strong free GTase activity of S. mutans grown in media similar to TTY broth or in a chemically defined medium.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…When S. mutans was grown in sucrosefree TTY broth, significantly higher GTase activity was detected in the culture supernatant as compared with several commercial broth media, except BHI (Table 2). Other investigators (3,11,16,23) also demonstrated strong free GTase activity of S. mutans grown in media similar to TTY broth or in a chemically defined medium.…”
Section: Resultsmentioning
confidence: 86%
“…Furthermore, it is of interest to note that many "purified" GTase preparations contain a tightly bound carbohydrate (probably glucan) moiety (2,4,20). However, low-molecular-weight GTase free of contaminating glucan may be obtained by growing the bacterium in a chemically defined sucrosefree medium (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HS6 cells grown in a sucrose-free broth were also used. It has been suggested that THB might contain small amounts of sucrose (21,24). The THB used in this experiment was found to contain 1.95 mg of glucose and 0.32 mg of sucrose per ml of broth, by gas-liquid chromatographical analysis.…”
Section: Methodsmentioning
confidence: 68%
“…Schachtele et al. (21) demonstrated that the GTF enzymes from strain 6715 grown in defined medium were stimulated 11-fold by soluble primer dextrans. Comparison of GTF activity of strain GS-5 at any point during growth indicated that these enzymes are not greatly stimulated by primer (data not shown).…”
Section: Discussionmentioning
confidence: 99%